Use of Biochar to Control Root-Feeding Soil Nematodes on Muna Local Tomatoes Variety - Ningsi, Fitri Wahyu; Hakim, Irfan; Dussy, Achmad Nur Azhary; Rahmaniar, Wa Ode; Yudistira, Yudistira; Kilowasid, Laode Muhammad Harjoni (JOURNAL OF TROPICAL SOILS, 2022)
Energy pathways in soil nematode communities consist of energy pathways for roots, bacteria, and fungi. The dominance of the root energy pathway indicated an increase in nematode attacks on the roots that can be regulated through changes in food availability and the environment. This study aimed to (i) determines the effect of the biochar rate on soil nematode energy pathways on local tomato plants and (2) determine the biochar rate that can suppress the dominance of root-feeding nematodes of local varieties of Muna tomato plants. The treatment tested was the biochar rate expressed as a percentage of the biochar weight the soil weight, namely 0%, 5%, 10%, and 15%. Each was repeated three times, randomly placed in the experimental plot following the randomized block design procedure. The results showed that the addition of biochar to 10% of the soil weight decreased the abundance of the total nematodes and family Longidoridae, on the other hand, increased Aphelenchoididae, Spearman rho correlation. The abundance of root eaters decreased; on the other hand, fungivores increased with the biochar rate. Spearman rho indicated that fungivores were negatively correlated with root-feeders and omnivores while positively correlated with predators. It was concluded that applying biochar up to a rate of 10% of the soil weight before planting could suppress the abundance of root-feeding nematodes in the vegetative growth phase of Muna local tomatoes variety.